2012
DOI: 10.1371/journal.pone.0044343
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor Enhances Calcium Regulatory Mechanisms in Human Airway Smooth Muscle

Abstract: Neurotrophins (NTs), which play an integral role in neuronal development and function, have been found in non-neuronal tissue (including lung), but their role is still under investigation. Recent reports show that NTs such as brain-derived neurotrophic factor (BDNF) as well as NT receptors are expressed in human airway smooth muscle (ASM). However, their function is still under investigation. We hypothesized that NTs regulate ASM intracellular Ca2+ ([Ca2+]i) by altered expression of Ca2+ regulatory proteins. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 54 publications
(83 reference statements)
2
50
0
Order By: Relevance
“…Finally, we measured the peak tonic contraction in response to CCh and SP, whereas in the mouse intestine and colon the contractile agonists elicited an increase in ongoing phasic contractions. It is noteworthy that similar to our findings in gut smooth muscle, preexposure of rat and human airway smooth muscle to BDNF causes an augmentation of muscarinic contractions (1,40,48,49,62).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Finally, we measured the peak tonic contraction in response to CCh and SP, whereas in the mouse intestine and colon the contractile agonists elicited an increase in ongoing phasic contractions. It is noteworthy that similar to our findings in gut smooth muscle, preexposure of rat and human airway smooth muscle to BDNF causes an augmentation of muscarinic contractions (1,40,48,49,62).…”
Section: Discussionsupporting
confidence: 89%
“…Thirdly, we used two TrkB-selective agonists, LM22A4 and 7,8-dihydroxyflavone (1,5,28), and showed that these resulted in augmentation of peak CCh contraction similar to that seen with BDNF (Fig. 4).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations